2023
DOI: 10.14429/dsj.73.18180
|View full text |Cite
|
Sign up to set email alerts
|

A Frequency Tunable Dielectric Resonator Antenna with Reduction of Cross Polarisation for Wi MAX and Sub 6 GHz 5G Applications

Rajkishor Kumar,
Avinash Chandra,
Naveen Mishra
et al.

Abstract: A frequency Tunable (mechanical tuning) Linearly Polarized (TLP) rectangular Dielectric Resonator Antenna(DRA) coupled with a horizontal/vertical-slot and excited with circular-ring type feed is investigated in this article.The frequency tunability (mechanical tuning) is achieved by the rotation of slot at different angles of the proposedstructure. Hence, two linearly polarized antennas have been proposed for different frequency bands such as Wi-MAX and Sub-6 GHz/5G, respectively, using slot variations (named … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Reduction in crosspolarization levels leads to improved signal purity and quality. 6 The higher co-pol values in Fig. 5 indicated that the designed CDRA effectively radiated the energy while minimizing the radiation in the orthogonal directions.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Reduction in crosspolarization levels leads to improved signal purity and quality. 6 The higher co-pol values in Fig. 5 indicated that the designed CDRA effectively radiated the energy while minimizing the radiation in the orthogonal directions.…”
Section: Resultsmentioning
confidence: 92%
“…DRAs, as specialized configurations of dielectric resonators, offer distinct advantages over traditional metallic counterparts, including reduced geometric dimensions, diminished weight, and cost-effectiveness, and this has propelled the exploration and utilization of microwave dielectric materials to optimize the design and functionality of DRAs, addressing the increasing demand for miniaturized and high-frequency communication systems. [3][4][5][6][7][8] DRAs are characterized by their diverse configurations, with the choice of geometry playing a crucial role in the antenna's performance and adaptability. Among the various configurations, such as rectangular, cylindrical, semi-hemispherical, and triangular, the cylindrical geometry holds particular significance due to its unique characteristics.…”
mentioning
confidence: 99%
“…However, it is worth noting that they may pose challenges in practical implementation due to the complexity of their feeding network. Another potential alternative could be the use of a dielectric resonator antenna [103].…”
Section: Methodsmentioning
confidence: 99%
“…where 2 and λ is the eigenvalue. Here, g and q are specified as the combination of m and n, and w g is the weighting function.…”
Section: Wave Equation Transformationmentioning
confidence: 99%
“…The antenna is an important component of any wireless apparatus. Different types of antennae, such as dipole, microstrip slot antenna, 1 leaky‐wave, dielectric resonator antenna, 2 Yagi‐Uda, and so on, have been widely used in wireless communication systems. Microstrip antenna (MA) has become popular and widely used as an efficient radiator due to its reliability, low weight, and integrability with solid‐state devices 3–6 .…”
Section: Introductionmentioning
confidence: 99%